2017
DOI: 10.1186/s12870-017-1055-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of DNA methylation, mRNAs, and small RNAs during maize embryo dedifferentiation

Abstract: BackgroundMaize (Zea mays) is an important model crop for transgenic studies. However, genetic transformation of maize requires embryonic calli derived from immature embryo, and the impact of utilizing tissue culture methods on the maize epigenome is poorly understood. Here, we generated whole-genome MeDIP-seq data examining DNA methylation in dedifferentiated and normal immature maize embryos.ResultsWe observed that most of the dedifferentiated embryos exhibited a methylation increase compared to normal embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Our comparison between the callus and the seedling uncovered globally elevated methylation in the callus in all three sequence contexts. Consistently, hypermethylation in the callus relative to the immature embryo was found in a study that used another maize inbred line and methylated DNA immunoprecipitation sequencing (MeDIP-seq) data 48 . In this study, 24 nt small RNA was shown to be positively correlated with DNA methylation.…”
Section: Discussionsupporting
confidence: 62%
“…Our comparison between the callus and the seedling uncovered globally elevated methylation in the callus in all three sequence contexts. Consistently, hypermethylation in the callus relative to the immature embryo was found in a study that used another maize inbred line and methylated DNA immunoprecipitation sequencing (MeDIP-seq) data 48 . In this study, 24 nt small RNA was shown to be positively correlated with DNA methylation.…”
Section: Discussionsupporting
confidence: 62%
“…The mapping rate in our study was similar to that in P . trichocarpa leaves (41.41%) [ 27 ], but much lower than that in rice (~85%), maize (~93%) and cotton (~95%) [ 24 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…High levels of DNA methylation increase induction in Coffea canephora [45] and embryogenic cell formation in Arabidopsis T87 [46]. The MeDIP-seq profiles of maize [19,47] and WGBS profiles of regenerated rice [40] show a similar decrease in methylation upon regeneration. The modulation in DNA methylation may signify its role in re-differentiation, where hormone ratios determine organ identity in regeneration [48].…”
Section: Modulation Of Dna Methylation In Culture Is Crucial To Regenmentioning
confidence: 88%
“…In sugarcane, disease-resistant somaclones are induced by demethylating agents, such as 5-azaC [29]. Similarly, somaclonal variations in maize [19,47], Arabidopsis [74], rice [40] and several plant species may result from changes in DNA methylation. Altering DNA methylation can generate somaclones, which may offer some economic benefit; however, somaclonal variations are inconsistent and non-reproducible.…”
Section: Discussionmentioning
confidence: 99%